Neonatal exposure to xenoestrogens impairs the ovarian response to gonadotropin treatment in lambs - Rivera, Oscar E. (2015)
Bisphenol A (BPA) and diethylstilbestrol (DES) are xenoestrogens which have been associated with altered effects on reproduction. We hypothesized that neonatal xenoestrogen exposure affects the ovarian functionality in lambs. Thus, we evaluated the ovarian response to exogenous ovine Follicle Stimulating Hormone (oFSH) administered from postnatal day 30 (PND30) to PND32 in female lambs previously exposed to low doses of DES or BPA (BPA50: 50 μg/kg.day, BPA0.5: 0.5 μg/kg.day) from PND1 to PND14. We determined: a) follicular growth, b) circulating levels of E2, c) steroid receptors (ERA, ERB, AR) and atresia, d) mRNA expression levels of the ovarian bone morphogenetic protein (BMPs) system (BMP6, BMP15, BMP receptor type 1B, GDF9) and FSH receptor (FSHR). Lambs neonatally exposed to DES or BPA showed an impaired ovarian response to oFSH with a lower number of follicles ≥2 mm together with a lower number of atretic follicles and no increase in E2 serum levels in response to oFSH treatment. In addition, AR induction by oFSH was disrupted in granulosa and theca cells of lambs exposed to DES or BPA. An increase in GDF9 mRNA expression levels was observed in oFSH-primed lambs previously treated with DES or BPA50. In contrast, a decrease in BMPR1B was observed in BPA0.5-postnatally exposed lambs. The modifications in AR, GDF9 and BMPR1B may be associated with the altered ovarian function due to neonatal xenoestrogen exposure in response to an exogenous gonadotropin stimulus. These alterations may be the pathophysiological basis of subfertility syndrome in adulthood.